The Successional Changes in the Gut Microbiome of Pasture-Raised Chickens Fed Soy-Containing and Soy-Free Diets - Lourenco, Jeferson M.; Rothrock Jr., Michael J.; Fluharty, Francis L.; Callaway, Todd R. (Frontiers in Sustainable Food Systems, 2019)
The succession of bacterial species as birds mature can impact their growth efficiency, health, and food safety due to the ability of a mature gastrointestinal microbial population to exclude opportunistic pathogenic bacteria from colonization. There has been an increase in the number of chickens fed a soy-free diet compared to the standard soybean-containing rations in pastured poultry. Therefore, the present study was designed to describe the impacts of feeding a soy-containing (SOY) or a soy-free diet (SF) on the bacterial succession in the gut of pasture-raised chickens. In order to compare microbiome compositions as birds aged, 16s rRNA gene sequencing was performed on the gastrointestinal tract of 1-day-old birds, on fecal material obtained at different ages, and on the cecal contents collected at slaughter from broilers fed each of the 2 diets. Results showed that at the phylum level, regardless of diet and birds’ stage of life, there was a predominance of the phylum Firmicutes, which ranged from 50 to 90% of all OTUs in all samples. Moreover, the number of observed OTUs significantly increased (P < 0.001) as birds in the SF diet grew older; however, no significant variations (P = 0.11) in this trait were observed as birds in the SOY diet aged. Shannon Diversity indices calculated for birds in both diets had greater values (P < 0.001) in the cecal contents of adult birds collected at slaughter, compared to samples obtained at earlier ages. Also in spite of which diet was offered, the abundance of Oscillospira, Faecalibacterium, Ruminococcus, and 2 unidentified genera from the orders Clostridiales and RF39 all increased as birds aged, while abundance of Lactobacillus decreased. The predicted metabolic functions using microbiome data showed no differences (P  0.26) in metabolism of amino acids, carbohydrates, lipids, and energy for both diets. These findings demonstrate that, under these experimental conditions, while diet modulates some microbial changes in the gut of pasture-raised chicken, overall, a similar successional pattern is observed for both diets. Moreover, the resulting metabolic functions are very similar between diets regardless of age.